The Impact of Obstructive Sleep Apnoea and Nasal Continuous Positive Airway Pressure on Circulating Ischaemia-Modified Albumin Concentrations - Firat Uygur; Hakan Tanriverdi; Murat Can; Tacettin Ornek; Fatma Erboy; Bulent Altinsoy; Figen Atalay; Murat Damar; Furuzan Kokturk; Meltem Tor (Mediators of Inflammation)
The aim of the present study was to evaluate the impact of obstructive sleep apnoea syndrome (OSAS) and the effects of nasal continuous positive airway pressure (CPAP) on circulating ischaemia-modified albumin (IMA) concentrations. The study included 97 newly diagnosed OSAS patients and 30 nonapnoeic controls. Blood samples were obtained in the morning after polysomnography. After 3 months of CPAP treatment, 31 patients with moderate-severe OSAS were reassessed for serum IMA concentrations. Significantly higher serum IMA concentrations were measured in the OSAS group than in the control group [0.518±0.091 absorbance units (ABSU), 0.415±0.068 ABSU, P<0.001]. Serum IMA concentrations correlated significantly with the apnoea-hypopnoea index, mean SaO2, desaturation index, and C-reactive protein concentrations. Multiple logistic regression analyses showed that OSAS increased the serum IMA concentration independent of age, sex, body mass index, smoking habit, and cardiovascular disease. After 3 months of treatment with CPAP, OSAS patients had significantly lower serum IMA concentrations (0.555±0.062 ABSU to 0.431±0.063 ABSU, P<0.001). The results showed that OSAS is associated with elevated concentrations of IMA, which can be reversed by effective CPAP treatment.